The effect of running experience and speed on local dynamic stability in running - Cerrito, A.; Wittwer, L.; Schmitt, K.-U. (Frontiers in Sports and Active Living, 2025)
Introduction: As a coach or health care professional working with physically active people, it can be difficult to guide runners towards safe and effective progression, because making changes to single aspects of running technique may not lead to the desired result. Alternatively, it has been proposed to consider the human body as one complex system when assessing and improving human movement. From this perspective, it appears that the movement variability and local dynamic stability, expressed as the maximum Lyapunov exponent (LyEmax), may be of particular interest. This study investigated the difference in LyEmax of the lower extremities' main joints (ankle, knee, hip) between experienced and novice runners at different running speeds.